2021
DOI: 10.3390/vaccines9101171
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 2 (KLF2) in Immune Cell Migration

Abstract: Krüppel-like factor 2 (KLF2), a transcription factor of the krüppel-like family, is a key regulator of activation, differentiation, and migration processes in various cell types. In this review, we focus on the functional relevance of KLF2 in immune cell migration and homing. We summarize the key functions of KLF2 in the regulation of chemokine receptors and adhesion molecules and discuss the relevance of the KLF2-mediated control of immune cell migration in the context of immune responses, infections, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…KLF2 (Krüppel-like factor 2) belongs to the Krüppel-like family of ZNF transcription factors and bears a Cys 2 His 2 ZNF-containing DNA binding domain. KLF2 is a key regulator of activation, differentiation, and migration processes in numerous cell types, including endothelial cells function and vascular homeostasis [ 98 ].…”
Section: Roles Of Host Znf Proteins In Covid-19mentioning
confidence: 99%
“…KLF2 (Krüppel-like factor 2) belongs to the Krüppel-like family of ZNF transcription factors and bears a Cys 2 His 2 ZNF-containing DNA binding domain. KLF2 is a key regulator of activation, differentiation, and migration processes in numerous cell types, including endothelial cells function and vascular homeostasis [ 98 ].…”
Section: Roles Of Host Znf Proteins In Covid-19mentioning
confidence: 99%
“…Of note, Klf2 seems to have oncogenic potential in our experimental model, being this report the first connection between this gene and sarcoma biology. Furthermore, KLF2, as an ERK5 downstream target, could be implicated in cancer through different mechanisms that remain unexplored, as could be the case of stem cell biology [ 65 , 66 ] or other processes such as inflammatory response [ 67 ], immune response [ 68 ], or angiogenesis [ 61 , 69 ]. Therefore, one possibility could be that the ERK5–KLF2 axis acts as a node in sarcoma biology by controlling several key processes.…”
Section: Discussionmentioning
confidence: 99%
“…KLF2 and KLF4 are assumed to play a central role in maintaining endothelial cell homeostasis and vascular health. Multiple studies have confirmed the atheroprotective effect of KLF2 and KLF4 through inhibition of inflammatory response [ 48 , 49 , 50 , 51 , 52 ]. The activator of KLF2 presented anti-inflammatory effects and attenuated the adhesion of monocytes to endothelial cells, which could be a promising therapeutic strategy for atherosclerosis [ 53 ].…”
Section: Zinc-related Proteinsmentioning
confidence: 99%